Two new species, Ophiopogon dolichocaulis and O. trigonantherus (Asparagaceae), from northern Vietnam - Nguyen, Khang Sinh; Tanaka, Noriyuki; Averyanov, Leonid V.; Maisak, Tatiana V.; Nguyen, Phuong Hanh; Tran, Duc Binh (Phytotaxa, 2021)
Two new species of Ophiopogon, O. dolichocaulis from Son La Province and O. trigonantherus from Cao Bang Province in northern Vietnam, are described and illustrated. The former is similar to O. chingii, while the latter is similar to O. rupestris and O. dracaenoides. This paper not only details their taxonomic features and relationships to similar species but also provides ecological data on their habitats and phenology.